Pengaruh Kualitas Pelayanan dan Promosi Terhadap Loyalitas Pelanggan Pengguna Grabfood Kota Bima - Nurfajriah, Putri; Ismunandar, Ismunandar; Amirulmukminin, Amirulmukminin (Universitas Serambi Mekkah, 2024)
This research aims to determine the quality of service and promotions on customer loyalty of Grabfood users in Bima City. This type of associative research uses primary data and comes from research instruments in the form of Likert scale questionnaires. The population used in this research is all GrabFood service users in Bima City. The appropriate sample size for research is between 30 and 500. So the number of samples in this research is 100 people with a sample determination technique, namely purposive sampling. Data collection in this research used observation, questionnaires and literature study. The data that has been collected will be analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, multiple correlation coefficients, determination tests, t tests and f tests. The research results show that service quality and promotion have a significant effect on customer loyalty with an influence of 52.7%.